WhatsApp-Based Speaking Test in EFL Context - Angela Bayu Pertama Sari (Journal of English Language Studies, 2020)
Prior studies had reported that the speaking test was quite troublesome. WhatsApp-based speaking test was one of the technology-enhanced assessment methods that became an option for more practical assessment.  It was a descriptive qualitative study that was conducted by investigating 145 non-English university students in Indonesia. Data collecting instruments were observation, documentation, and open-ended questionnaires. Then, the data analysis used descriptions on each category. The result exposed that 50.3% of the overall student was somewhat satisfied with the implementation of the WhatsApp-based speaking test. The study reported five significant students’ positive responses to the test.  Those positive responses were that it was considered as a fun-based test. It created an opportunity for the students to improve their language performance, it was also a time-saving test and it built a test environment that was less pressured and less anxious for the students. Then, the test was more appropriate for the students who belonged to the post-millennial generation. Also, the next finding of this study revealed three students’ negative responses towards the implementation of WhatsApp-based speaking tests in English classes. Those three prominent responses were the students disturbed by the noisy atmosphere during the test, the students encountered some technical problems on the test, and the students were still quite nervous during the test due to it was their first experience in doing the WhatsApp-based speaking test.